2017
DOI: 10.3389/fimmu.2017.01049
|View full text |Cite
|
Sign up to set email alerts
|

Class A CpG Oligonucleotide Priming Rescues Mice from Septic Shock via Activation of Platelet-Activating Factor Acetylhydrolase

Abstract: Sepsis is a life-threatening, overwhelming immune response to infection with high morbidity and mortality. Inflammatory response and blood clotting are caused by sepsis, which induces serious organ damage and death from shock. As a mechanism of pathogenesis, platelet-activating factor (PAF) induces excessive inflammatory responses and blood clotting. In this study, we demonstrate that a Class A CpG oligodeoxynucleotide (CpG-A1585) strongly induced PAF acetylhydrolase, which generates lyso-PAF. CpG-A1585 rescue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

6
3

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 48 publications
0
12
1
Order By: Relevance
“…Unlike type-B CpG sequences, the type-A CpG ODNs are poor activators of NF-κB signaling and cytokines such as IL-6 and IL-10. 40 While recent study showed that injections of CpG(A) alleviated severity of sepsis in mice by reducing blood clotting, 41 the control CpG(A)-scrRNA did not show anti-inflammatory activity in our experiments. The presence of functional miR-146a-5p guide strand in the CpG conjugate was key to the biological activity of this oligonucleotide.…”
Section: Discussioncontrasting
confidence: 59%
“…Unlike type-B CpG sequences, the type-A CpG ODNs are poor activators of NF-κB signaling and cytokines such as IL-6 and IL-10. 40 While recent study showed that injections of CpG(A) alleviated severity of sepsis in mice by reducing blood clotting, 41 the control CpG(A)-scrRNA did not show anti-inflammatory activity in our experiments. The presence of functional miR-146a-5p guide strand in the CpG conjugate was key to the biological activity of this oligonucleotide.…”
Section: Discussioncontrasting
confidence: 59%
“…The purified total RNA was reverse-transcribed using a PrimeScript TM RT Master Mix (TaKaRa Bio Inc., Osaka, Japan) according to the manufacturer's instructions. Quantitative PCR (qPCR) reactions were performed as described previously (27). Primers for the transcripts encoding β-actin, IL-4, and IFN-γ were purchased from TaKaRa Bio, Inc.…”
Section: Gene Expression Analysismentioning
confidence: 99%
“…Quantitative PCR (qPCR) was performed as described previously 17,18 . Primers for five genes (encoding IFN-γ, TNF-α, IL-1β, IL-6, and IL-17) were obtained from TaKaRa Bio, Inc. Alexa Fluor ® 488 anti-mouse CD4 (CAT# 100423; BioLegend) and PerCP/Cy5.5 anti-mouse IL-17A antibodies (CAT# 506919; BioLegend) were used.…”
Section: Cytokine Assaymentioning
confidence: 99%